1978
DOI: 10.1111/j.1469-8137.1978.tb01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Soils, Vegetation Development and Heavy Metal Tolerance in Plant Populations From Metalliferous Areas

Abstract: SUMMARYThe development of vegetation (mainly the Violetum calaminariae Schwick.) in heavy metalcontaminated areas depends on the metals mobility in soils and on metal availability for plants. Moreover, the ability of plant populations to evolve metal tolerance is one of the most important characters which determines the structure, density and development of the vegetation in such areas. In this work, metal mobility in soils and availability to plants in both calcareous and non-calcareous situations were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 10 publications
2
47
1
Order By: Relevance
“…In a study of plants colonizing the lead-and zinccontaminated area of Plombi~res in Belgium, Simon (1978) stated that Betula pendula and Salix caprea only occur in areas containing relatively low levels of lead and zinc, but high concentrations of calcium.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of plants colonizing the lead-and zinccontaminated area of Plombi~res in Belgium, Simon (1978) stated that Betula pendula and Salix caprea only occur in areas containing relatively low levels of lead and zinc, but high concentrations of calcium.…”
Section: Introductionmentioning
confidence: 99%
“…The two other sites showed lower metal concentrations, which can be explained by the reclamation work for the Les Malines mine and by the different nature of the ore envelope at Petra Alba. Some other European mining sites have also shown such outstandingly high concentrations of total Zn, Cd and Pb, for instance the Trelogan mine (UK) where soil metal concentrations reached 95,000 mg kg -1 Zn, 40,000 mg kg -1 Pb and 267 mg kg -1 Cd (Bradshaw and Chadwick 1980) or in Belgium where mine deposits at Plombières and La Calamine are also highly contaminated with zinc (19,000 and 101,000 mg kg -1 , respectively) and lead (35,000 and 9,000 mg kg -1 , respectively) (Assuncao et al 2003;Simon 1978). Soils around smelters can also contain large amounts of heavy metals.…”
Section: Mine Soils and Metal Concentrationsmentioning
confidence: 99%
“…This has been demonstrated experimentally (Bradshaw, McNeilly and Gregory, 1965;Baker, 1978;Cox and Hutchinson, 1979;Karataglis, 1980). In contrast, calcareous metalliferous spoil not grossly polluted by heavy metals can support a diversity of wildlife habitats (Simon, 1978;Holliday, Johnson and Bradshaw, 1979;LeFebvre and Simon, 1979) including regionally rare plants of conservation value (Johnson, 1978;Johnson, Putwain and Holliday, 1978). Simon (1978) showed that the vegetation cover and level of genetic tolerance to heavy metals of colonizing species on calcareous metalliferous spoil corresponded to the level of soil toxicity as expressed by the ratio lead/calcium.…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, calcareous metalliferous spoil not grossly polluted by heavy metals can support a diversity of wildlife habitats (Simon, 1978;Holliday, Johnson and Bradshaw, 1979;LeFebvre and Simon, 1979) including regionally rare plants of conservation value (Johnson, 1978;Johnson, Putwain and Holliday, 1978). Simon (1978) showed that the vegetation cover and level of genetic tolerance to heavy metals of colonizing species on calcareous metalliferous spoil corresponded to the level of soil toxicity as expressed by the ratio lead/calcium. Similarly Wilkins (1957) showed that the lead tolerance index of plant populations increased with the addition of calcium to culture solutions.…”
Section: Introductionmentioning
confidence: 99%